Gambaran Kesadaran, Akses Informasi, dan Pengalaman terkait Layanan Kesehatan Mental pada Masyarakat di Indonesia - Putri, Mirasstity Akacia; Bimantoko, Iqbal; Herton, Nezzia; Listiyandini, Ratih Arruum (Jurnal Online Psikogenesis, 2023)
The study aims to examine mental health issues in Indonesia in several aspects including individuals’ awareness of mental health, individuals’ experience when accessing mental health information, services, and treatment as well as maintenance behavior after receiving treatment. This study is conducted using the cross-sectional method with a quantitative approach. The survey was distributed via social media platforms, and was completed by a total of 406 participants, ranging from 18-25. Data were then analyzed using the descriptive analysis technique.  Findings of the study include: 1) individuals’ awareness of the issue surrounding mental health was relatively high, 2) accessibility of mental health information was good although, may be further improved, 3) stigma surrounding mental disorders, financial hardships, and poor access to mental health professionals/therapists, are the deterring factors for receiving treatments, 4) there are many strategies to improve treatment satisfaction, such as community-based interventions, bettering the quality of digital mental health platforms, as well as the quality and quantity of mental health professionals across Indonesia. Overall, despite high individual awareness of mental health and accessibility to mental health information, there were many gaps identified within the mental health care in Indonesia that can massively benefit from interventional programs.